Profile of Students' Ability to Understand the Intrinsic Elements of Elementary School Class V Stories in the Independent Curriculum - Nuro’ifah, Siti; Istiq'faroh, Nurul; Subrata, Heru; Purwoko, Budi (Papanda Publisher, 2025)
This study aims to profile the ability of fifth-grade elementary school students in understanding the five key intrinsic elements of stories characters, setting, plot, theme, and moral message within the context of the Merdeka Curriculum. Using a qualitative descriptive approach, the research was conducted at SDN Terik, Krian District, involving 26 students selected through purposive sampling. Data were collected through interviews, observations, and written tests, then analyzed using qualitative descriptive methods. The findings indicate varying levels of comprehension among students, with characterization (identified correctly by 73% of students) being the easiest element to understand, while plot and moral message (understood correctly by only 19% of students) were the most challenging. Factors such as reading interest and the use of audiovisual media significantly influenced students’ understanding. However, limited learning time, lack of diverse teaching methods, and differing literacy levels posed challenges. The study highlights the importance of innovative, multimodal teaching strategies and the integration of contextual learning experiences to improve students’ literacy skills. These findings contribute valuable insights for educators seeking to enhance the effectiveness of language and literature learning in accordance with the principles of the Merdeka Curriculum.